Suitability of Piperacillin–Tazobactam for Treating Dogs Infected with Extended-Spectrum β-Lactamase-Producing Enterobacterales: Pharmacokinetic and Pharmacodynamic Analysis - Kazuki Harada; Hyo Harada; Yuka Kanao; Mizuki Kusumoto (Antibiotics)
Background/Objectives: Piperacillin–tazobactam (TZP) is a potential alternative to carbapenems for the treatment of dogs infected with extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E), but its efficacy remains unestablished. In this study, pharmacokinetic–pharmacodynamic (PK/PD) analysis was performed to estimate the clinical efficacy of TZP against ESBL-E infections in dogs. Methods: We determined the minimum inhibitory concentrations (MICs) of TZP in canine ESBL-E isolates, including Escherichia coli (n = 62), Klebsiella pneumoniae (n = 89), and Enterobacter cloacae (n = 31), using agar dilution. Monte Carlo Simulation (MCS) was performed to estimate the probability of target attainment (PTA) based on the PK/PD characteristics of TZP. Results: The MICs that can inhibit the growth of 90% of the isolates for the three bacterial species were determined as 16/4 µg/mL. MCS analysis revealed that the piperacillin PK/PD cutoff values (highest MICs with a PTA ≥90%) were ≤0.031, ≤0.5, and ≤2 μg/mL at a bolus dose of 50 mg/kg TZP (44.4 mg/kg piperacillin) every 12, 8, and 6 h (q12h, q8h, and q6h), respectively. The cumulative fractions of response were ≤90% based on the MIC distribution of ESBL-producing E. coli, K. pneumoniae, and E. cloacae isolates from dogs: 1.60, 0.48, and 0.15% at q12h; 32.56, 14.57, and 9.65% at q8h; and 74.51, 45.85, and 43.92% at q6h, respectively. Conclusions: We believe that TZP is not recommended for the treatment of canine ESBL-E infections, except for cases with a lower MIC than the PK/PD cutoff values determined in this study.